Pengaruh Latihan Kihon terhadap Peningkatan Teknik Kata pada Atlet Karate di Dojo Ozaka Karate Club (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of kihon training on improving kata techniques among karate athletes at Dojo Ozaka Karate Club. Kihon, as the fundamental technique of karate, plays a crucial role in developing kata skills, which include aspects such as movement accuracy, balance, strength, rhythm, and energy expression (kime). This research employed a quantitative approach with an experimental method using a one-group pretest–posttest design. The population consisted of all karate athletes actively training at Dojo Ozaka Karate Club, while the sample comprised 20 athletes selected through purposive sampling. Data collection instruments included kata performance tests, observations, and documentation. Data were analyzed descriptively and comparatively to examine differences in kata technique scores before and after kihon training. The findings show an improvement in kata technique abilities following intensive kihon training. Athletes who previously had difficulties with stances, punching accuracy, and kicking power demonstrated significant improvements after participating in continuous basic training programs. This confirms that kihon training has a positive effect on improving kata techniques in karate athletes. The study is expected to serve as an evaluation material for coaches in designing more effective training programs, particularly in strengthening basic skills to support optimal kata performance.